Physicochemical properties and fatty acids composition of Sudanese Baobab (Adansonia Digitata L.) Seed oil - Abeer A. Idris; Azhari H. Nour; Mahmoud M. Ali; Ibrahim Y. Erwa; Omer A. Omer Ishag (International Journal of Pharma and Bio Sciences, 2020)
Baobab (Adansonia digitata) is a widespread tree species of the genus Adansonia, native to the African continent. The tree has multi-purpose uses, as it produces food and non-food products such as medicines and fuel. The global demand for baobab raw material for industrial applications has increased dramatically in recent years, thereby increasing their commercial value and importance. The aim of this study was to characterize the physicochemical properties and fatty acid composition of A. digitata seed oil. The oil is extracted by Soxhlet using n-hexane. The physicochemical properties of the seed oil were assessed by standard and established methods. The fatty acid composition of the seed oil was determined by GC-MS. The reddish yellow with characteristic odor oil obtained from the seeds had the following physicochemical properties: yield, 33.83%; melting point, 8 °C; boiling point, 227 °C; refractive index (25 °C), 1.436; iodine value, 98.3 g/100 g of oil; peroxide value, 4.3 meq. O2/kg of oil; free fatty acids, 0.34%; acid value, 6.8 mg of KOH/g of oil; saponification value, 180.7 mg KOH/g of oil; unsaponifiable matter, 1.7; moisture and volatile value, 14.79 (wt%); density, 0.867 g/cm3; viscosity, 35.03 mm2/s; specific gravity, 0.874. The fatty acids composition showed that linoleic acid (30.63%) was the major fatty acid and followed by oleic- (23.34%), palmitic- (22.87%), stearic- (5.89%), malvalic- (5.52%), cis-10-nonadecenoic- (2.67%), sterculic- (1.61%) and arachidic acid (1.43%). Therefore, more and advanced research should be undertaken for this abundant source of natural oil for possible industrial applications.